Collaborative idea exchange and material tinkering influence families' creative engineering practices and products during engineering programs in informal learning environments. Issue 9 (11th May 2021) - Kim, Soo Hyeon; Zimmerman, Heather Toomey
Abstract : Purpose: This paper aims to investigate how families' sociomaterial experiences in engineering programs held in libraries and a museum influence their creative engineering practices and the creativity expressed in their products derived from their inquiry-driven engineering activities. Design/methodology/approach: This research project takes a naturalistic inquiry using qualitative and quantitative analyses based on video records from activities of 31 parent–child pairs and on creativity assessment of products that used littleBits as prototyping tools. Findings: Families engaged in two sociomaterial experiences related to engineering – collaborative idea exchange and ongoing generative tinkering with materials – which supported the emergence of novel ideas and feasible solutions during the informal engineering programs. Families in the high novelty score group experienced multiple instances of collaborative idea exchange and ongoing generative tinkering with materials, co-constructed through parent-child collaboration, that were expansive toward further idea and solution generation. Families in the low novelty score group experienced brief collaborative idea exchange and material tinkering with specific idea suggestions and high involvement from the parent. An in-depth case study of one family further illustrated that equal engagement by the parent and child as they tinkered with the technology supported families' creative engineering practices. Originality/value: This analysis adds to the information sciences and learning sciences literatures with an account that integrates methodologies from sociocultural and engineering design research to understand the relationship between families' engagement in creative engineering practices and their products. Implications for practitioners include suggestions for designing spaces to support families' collaborative idea exchange and ongoing generative tinkering to facilitate the development of creative engineering practices during short-term engineering programs.